Analisis Jurnalisme Investigasi Dalam Film Collective (2019) - Muhammad Adib Syamuroma; Fifi Hasmawati; Ahmad Harun Yahya (Social Science and Contemporary Issues Journal, 2024)
This research is entitled Analysis of "Investigative Journalism in Film Collective (2019)". The research uses descriptive qualitative research methods. Collective film which is a collection of documentary results covering investigations into poor health facilities in Romania. The purpose of this research is to find out the investigation process in the film. This research uses qualitative methods with investigative journalism theory. The results of this research show that there are 5 investigative processes in the film, including: Collecting Documents, Searching for Physical Evidence, Searching for Witnesses, Writing a Report, and finally Publication. However, this film only explores 3 investigative processes, namely searching for physical evidence, collecting documents and searching for witnesses. This is considered reasonable, if this film only focuses on these three processes, because if these three processes are incomplete then investigative journalists cannot write results reports and publications. Because, all three are related to each other, this proves that investigative journalists carry out multiple verifications, not just one verification.